New perspective on creating web pages with HTML - Carey, Patrick (Cambridge, Massachusetts : Course Technology Cengage Learning, 1999)
Part of our New Perspectives Series, this text offers a case-oriented, problem-solving approach to learning how to create web pages with HTML. This Comprehensive title covers the basic to more advanced HTML and web page creation skills -- from creating and designing a Web page to programming with JavaScript and adding multimedia to a Web page.
Creating Web Pages with HTML Level I Tutorials -- Creating Web Pages with HTML Level II Tutorials -- Creating Web Pages with HTML Level III Tutorials
Includes index.
Keywords: HTML (DOCUMENT MARKUP LANGUAGE)